Aortic arch atheroma and the risk of stroke: a meta‐analysis. Issue 3 (August 2014) - Cui, Xiaoyang; Li, Yi; Liu, Junfeng; He, Sha; Liu, Ming
Abstract Backgrounds and objectives Epidemiological studies have suggested that aortic atheroma may play a role in cerebral embolization; however, no meta‐analysis was conducted to evaluate the relationship between aortic atheroma and risk of stroke. The aim of this study was to investigate the association between the presence of aortic atheroma and risk of stroke. Methods We performed a comprehensive search of observational studies reporting the relationship between the presence of aortic atheroma and stroke using the PubMed, EMbase, the China National Knowledge Infrastructure database (CNKI), Chinese Technical Periodicals (VIP), and WanFang Data databases. Two reviewers independently assessed the eligibility and extracted data from the included studies. We performed the meta‐analysis to estimate the strength of the association according to Meta‐analysis of Observational Studies in Epidemiology (MOOSE) guideline and assessed the study quality by the Newcastle‐Ottawa Scale (NOS). Results We identified 12 eligible studies with 3918 participants. The scores of the NOS of the included studies ranged from 5 to 9. The pooled estimate of strength of the association between the presence of aortic atheroma and stroke was statistical significant (OR = 3.93, 95%CI 2.86 to 5.40). In subgroup analysis according to plaques' morphology, complex aortic atheroma had significantly higher (OR = 5.90, 95%CI 4.14 to 8.41) risk of stroke than protruding atheroma (OR = 3.75, 95%CI 3.05 to 4.61). Conclusions This study indicated that aortic atheroma significantly increased the risk of stroke by about four times. Patients with complex aortic atheroma have a higher risk of stroke than protruding atheroma.